The level of religious motivation of aspirants, postulants and novices of the adoration congregation, India - Kainikunnel, Elizabeth Kurian (Animo Repository, 1994)
This study determines the level of religious motivation of the aspirants, postulants, and novices of the Congregation of the Sisters of the Adoration of the Blessed Sacrament. The subjects of the study were the total population of 57 in the three stages of formation of the province of Thalasserry of the SABS in India. Of the total respondents, 17 were aspirants, 16 were postulants, and 24 were novices. The descriptive cross-sectional research design was used. Data were collected using the Religious Motivation Questionnaire (RMQ). Means and standard deviations were computed to determine the levels of motivation. One-way ANOVA was used to assess the difference of the factors among the three groups of formation. The results showed that the respondents, as a whole, had an average level of religious motivation. It increased slightly as the candidates moved from one stage of formation to the other. A significant increase in the motive of Christian perfection was found through the stages of formation. There was a downward trend in the motive of service. No significant difference was observed in the motive of sacrificial worship. The study arrived at the following conclusions: (1) The motive of perfection significantly increased according to the stages of formation and (2) The novices expressed a higher level of motivation for religious life than aspirants and postulants. It is recommended that:1. At different stages of formation such as admission to the postulancy and before the first profession of the vows, assessment of motivation be seriously considered and,2. Since the downward trend in the motivation for service was observed, special orientation, more sessions, and exposure to the different fields of service which would facilitate greater awareness and clarification of religious motivation in this area be included in the total formation program.